Phase Separation Behavior and System Properties of Aqueous Two-Phase Systems with Polyethylene Glycol and Different Salts: Experiment and Correlation. (24th February 2015) - Yuan, Haihua; Liu, Yang; Wei, Wanqian; Zhao, Yongjie
Abstract : The phase separation behaviors of PEG1000/sodium citrate, PEG4000/sodium citrate, PEG1000/ammonium sulfate, and PEG4000/ammonium sulfate aqueous two-phase systems were investigated, respectively. There are two distinct situations for the phase separation rate in the investigated aqueous two-phase systems: one state is top-continuous phase with slow phase separation rate and strong bottom-continuous phase with fast phase separation rate and weak volume ratio dependence. The system properties such as density, viscosity, and interfacial tension between top and bottom phases which have effects on the phase separation rate of aqueous two-phase systems were measured. The property parameter differences between the two phases increased with increasing tie line length and then improved the phase separation rate. Moreover, a modified correlation equation including the phase separation rate, tie line length, and physical properties of the four aqueous two-phase systems has been proposed and successfully tested in the bottom-continuous phase, whose coefficients were estimated through regression analysis. The predicted results of PEG1000/sodium citrate aqueous two-phase systems were verified through the stationary phase retention in the cross-axis countercurrent chromatography.